Assessment of the effectiveness of topical propranolol 4% gel for infantile hemangiomas. (February 2017) - Mashiah, Jacob; Kutz, Ana; Rabia, Smail Hadj; Ilan, Efrat Bar; Goldberg, Ilan; Sprecher, Eli; Harel, Avikam
Abstract: Background: Infantile hemangiomas (IHs) are the most common vascular tumors in children. Because of their benign character and natural involution, the vast majority of IHs do not require any treatment. In the past few years, topical beta blockers have been reported to be an effective treatment of superficial IHs. Objective: We sought to evaluate the clinical effectiveness and safety profile of topical propranolol 4% gel for the treatment of IHs. Methods: A retrospective study of all cases of IHs treated with topical propranolol 4% gel between 2013 and 2015 was performed. All patients were evaluated in a pediatric dermatology unit of a tertiary medical center. Epidemiologic, clinical, and treatment data, including effectiveness score and safety, were reviewed. Results: The study included 63 patients with a total of 75 IHs. Of the total number of IHs, 43 (57.3%) showed a good response to treatment, 19 (25.3%) a partial response, and 13 (17.33%) poor or no response, thus 62 (82.6%) had good or partial response to treatment. Age at treatment initiation, treatment time, thickness of the superficial component, and size of the lesions were shown to predict response to therapy. Out of the entire examined group, only two patients reported minor local side effects manifested by irritation, redness, and scaling of the treated area. No systemic adverse effects were reported. Limitations: This is an uncontrolled retrospective study. Conclusion: Propranolol 4% gel is a safe and efficient topical therapy for IH.